Optimal timing of appendectomy in the pediatric population - Gurien, Lori A.; Wyrick, Deidre L.; Smith, Samuel D.; Dassinger, Melvin S. (The Journal of surgical research, 2016)
No consensus has been reached on optimal timing for performing appendectomies. We compared immediate and delayed appendectomies in pediatric patients presenting with suspected acute appendicitis to determine differences in postsurgical complications and perforation rates. A retrospective cohort study was performed of all children who underwent appendectomy during a 4-y period. Cutoffs used were 6, 8, and 12 h from admission to operating room (OR). The Student t-tests and chi-square tests were performed to compare continuous and categorical variables, respectively. A logistic regression model was fitted to determine predictors of appendiceal perforation. P values <0.05 were considered significant. Analysis included 484 patients with mean elapsed time from admission to OR of 394 min, with 262 subjects in the immediate and 222 subjects in the delayed >6 h groups. Surgical site infections (SSIs), perforations, and small bowel obstructions were similar between groups, and no statistically significant differences were found for SSIs in the nonperforated delayed versus immediate groups (P = 0.964). Time from admission to the OR did not predict perforation (P = 0.921), although white blood cell count at the time of admission was a significant predictor of perforation (odds ratio, 1.08; P < 0.001). For suspected acute appendicitis, delaying appendectomy after admission for >6 h demonstrated no differences in SSI or perforation rates compared with immediate appendectomy. Waiting to perform an appendectomy until the following day has equal outcomes to immediate surgical procedure and may improve overall quality of patient care by limiting surgeon fatigue.